2016
DOI: 10.1007/s10719-016-9736-5
|View full text |Cite
|
Sign up to set email alerts
|

The “in and out” of glucosamine 6-O-sulfation: the 6th sense of heparan sulfate

Abstract: The biological properties of Heparan sulfate (HS) polysaccharides essentially rely on their ability to bind and modulate a multitude of protein ligands. These interactions involve internal oligosaccharide sequences defined by their sulfation patterns. Amongst these, the 6-O-sulfation of HS contributes significantly to the polysaccharide structural diversity and is critically involved in the binding of many proteins. HS 6-O-sulfation is catalyzed by 6-O-sulfotransferases (6OSTs) during biosynthesis, and it is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 168 publications
1
78
0
Order By: Relevance
“…How Sulf2 participates in the control of Olig2+ AP generation remains to be established. Sulf2, together with Sulf1, are recognized as critical regulators of heparan sulfate (HS) activities through their ability to catalyze specific 6‐O‐desulfation of the polysaccharide (El Masri et al, ). HS, found at the cell surface and in the extracellular matrix, interact with many signaling cues and a major determinant of specificity and affinity of HS‐ligand interactions is 6‐O‐sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…How Sulf2 participates in the control of Olig2+ AP generation remains to be established. Sulf2, together with Sulf1, are recognized as critical regulators of heparan sulfate (HS) activities through their ability to catalyze specific 6‐O‐desulfation of the polysaccharide (El Masri et al, ). HS, found at the cell surface and in the extracellular matrix, interact with many signaling cues and a major determinant of specificity and affinity of HS‐ligand interactions is 6‐O‐sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…Some protein activity does not seem to require specific saccharide sequences . However, some do, even requiring the rarer 3‐ O ‐sulfate group, although the majority appear to use N ‐ and 2‐ O ‐sulfates . The most abundant disaccharide unit in heparin consists of a 2S iduronate linked to an N ‐ and 6‐ O ‐sulfated glucosamine.…”
Section: Hs Codesmentioning
confidence: 99%
“…[31] However, some do, even requiring the rarer 3-O-sulfate group, although the majority appear to use Nand 2-O-sulfates. [32] The most abundant disaccharide unit in heparin consists of a 2S iduronate linked to an Nand 6-O-sulfated glucosamine. For the biochemist, the inherent "stickiness" of HS makes the determination of its essentialness a fraught process.…”
Section: Hs Codesmentioning
confidence: 99%
“…How Sulf2 controls production of this AP subtype remains to be determined. Sulf2 is recognized as a critical regulator of signalling cues important in development, including FGFs, Wnt and BMPs (El Masri et al, 2017). Through its ability to catalyze specific 6-O-desulfation on HS chains, Sulf2 modulates signalling activities in many different ways, regulating either ligand secretion, processing and access to receptors (Rosen and Lemjabbar-Alaoui, 2010).…”
Section: Sulf2 a Specific Player In Regulating Generation Of Olig2-ementioning
confidence: 99%
“…Sulf1, by eliminating 6O sulfate groups on HS chains, locally lowers Shh/HSPG interaction and thereby promotes Shh release at the right time to trigger OPC specification from Olig2-expressing pMN cells (Touahri et al, 2012;Al Oustah et al, 2014). Jiang and collaborators (2017) more recently reported that Sulf2, the second member of the Sulf protein family (El Masri et al, 2017), plays a similar role as Sulf1 in triggering the MN to OPC fate change. In the present work, we also investigated the function of Sulf2 in the control of gliogenesis and came to the different conclusion that Sulf2 is dispensable for OPC production.…”
Section: Introductionmentioning
confidence: 99%